Phytochemical Composition and Comparative Antioxidant Activity of Leaf and Stem Bark Extracts of Glochidion arborecens Using DPPH and ABTS Assays - H. Haryoto; Edtano Trinanda; Broto Santoso; Muhammad Dohir Siaga Nagara; Novian Liwanda; Waras Nurcholis (Chemical Engineering Transactions)
This study explores the phytochemical composition and antioxidant activity of ethanol extracts from the leaves and stem bark of Glochidion arborescens. Extraction yielded 2.68% from leaves and 1.72% from stem bark. Phytochemical screening revealed the presence of flavonoids, tannins, and saponins, while steroids and triterpenoids were absent. Antioxidant activity was evaluated using DPPH and ABTS assays, with vitamin C as the positive control. The extracts demonstrated significant antioxidant potential, with IC50? values of 75.25 µg/mL and 74.92 µg/mL in the DPPH assay for leaves and stem bark, respectively. For the ABTS assay, IC50? values were 42.40 µg/mL for leaves and 34.00 µg/mL for stem bark. These findings indicate that the antioxidant activity of G. arborescens depends on the plant part and assay method used. The results provide valuable insights into the antioxidant properties of G. arborescens, emphasizing its potential pharmacological applications as a natural source of antioxidants. Future research should investigate the mechanisms underlying these antioxidant effects and assess their therapeutic potential in in vivo models. This study contributes to the growing body of knowledge on plant-derived antioxidants and their relevance in combating oxidative stress-related diseases.